Stakeholder Relations and the Persistence of Corporate Financial Performance - CHOI, Jaepil (Institutional Knowledge at Singapore Management University, 2009)
We examine the effect of a firm's relations with its nonfinancial stakeholders, including its employees, suppliers, customers, and communities, on the persistence of both superior and inferior financial performance. In particular, integrating and extending the resource-based view of the firm and stakeholder management literatures, we develop the arguments that good stakeholder relations not only enable a firm with superior financial performance to sustain its competitive advantage for a longer period of time, but more importantly, also help poorly performing firms to recover from disadvantageous positions more quickly. The arguments are supported by the analysis of a series of first-order autoregressive models. Our findings further suggest that the positive effect of good stakeholder relations on the persistence of superior performance is not as strong as that of some other firm resources, such as technological knowledge, but it is the only factor examined that promises to help a firm recover from inferior performance. Therefore, the role of positive stakeholder relations in helping poorly performing firms recover is found to be more critical than its role in helping superior firms sustain their performance advantage.